Association between atopic dermatitis and risk of stroke: a systematic review and meta-analysis - Hong Pan; Qing-Ping Han; Min-Ling Zeng; Fang Wang; Ying Xiong; Bo Wu; Hai-Ying Yu (Frontiers in Neurology)
Background/objectivesRecent studies have sought to determine the correlation between atopic dermatitis (AD) and the occurrence of stroke; however, these investigations have not reached a consensus. Consequently, our team conducted this meta-analysis and systematic review to further explore the potential relationship between these two conditions.MethodsA comprehensive literature search was conducted across PubMed, Embase, and Web of Science from their inception until January 2025 to identify observational studies examining the association between atopic dermatitis and stroke risk. Random-effects meta-analyses were performed using the generic inverse variance method, and hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated. Additionally, sensitivity analyses and subgroup analyses were conducted to assess the stability of the results and explore potential sources of heterogeneity.ResultsThis meta-analysis included 12 observational studies, comprising 8 cohort studies, 2 case–control studies, and 3 cross-sectional studies, with a total of 14,517,146 participants. The analysis revealed a significant correlation between AD and the risk of stroke (n = 17, OR = 1.27, 95%CI = 1.14–1.43). Subgroup analyses indicated a particularly strong association among males (n = 3, OR = 1.31, 95% CI = 1.07–1.60) and in the context of ischemic stroke types (n = 5, OR = 1.14 95%CI = 1.00–1.30). Furthermore, sensitivity analyses demonstrated that the results were stable and reliable.ConclusionAD is independently associated with an increased risk of stroke, especially in men, and there is a notable association with ischemic stroke. Moreover, the risk appears to be positively correlated with the severity of AD.Systematic review registrationIdentifier INPLASY202550006.